2008
DOI: 10.1080/13554790802108380
|View full text |Cite
|
Sign up to set email alerts
|

A left basal ganglia case of dynamic aphasia or impairment of extra-language cognitive processes?

Abstract: We report the case of OTM who presented with dynamic aphasia following a stroke that occurred in the left basal ganglia. He showed drastically reduced spontaneous speech in the context of well preserved naming, repetition and comprehension skills. OTM was particularly impaired in generating words, sentences and phrases when cued by a stimulus allowing many response options. By contrast, when a single response was strongly suggested by a stimulus, he could generate verbal responses adequately. OTM's non-verbal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…This pattern of decreasing speech rate with overt visual cues available with different genre type is consistent with the external support findings discussed below. Finally, the LH deficit is consistent with investigations of dynamic aphasia that highlight crucial brain areas underpinning conceptual preparation processes for propositional language (e.g., left basal ganglia, Crescentini et al, 2008;left inferior frontal, Robinson et al, 1998left inferior frontal, Robinson et al, , 2005. However, at present it is unclear how this relates to studies that have demonstrated a role of the subthalamic nuclei in proposition speech (e.g., Castner et al, 2007Castner et al, , 2008.…”
Section: Genressupporting
confidence: 68%
See 3 more Smart Citations
“…This pattern of decreasing speech rate with overt visual cues available with different genre type is consistent with the external support findings discussed below. Finally, the LH deficit is consistent with investigations of dynamic aphasia that highlight crucial brain areas underpinning conceptual preparation processes for propositional language (e.g., left basal ganglia, Crescentini et al, 2008;left inferior frontal, Robinson et al, 1998left inferior frontal, Robinson et al, , 2005. However, at present it is unclear how this relates to studies that have demonstrated a role of the subthalamic nuclei in proposition speech (e.g., Castner et al, 2007Castner et al, , 2008.…”
Section: Genressupporting
confidence: 68%
“…Procedural tasks facilitate concept selection because task topics are often habitual events or actions and are verbally rehearsed (Bartels-Tobin & Hinckley, 2005). Familiarity of topic tasks minimises the need to construct a novel message, as demonstrated by patient OTM who presented with dynamic aphasia and intact procedural discourse (Crescentini et al, 2008;see below). At the same time, the need to organise steps may place greater demands on sequencing.…”
Section: Investigating Propositional Speech: Genresmentioning
confidence: 97%
See 2 more Smart Citations
“…The BG is implicated in higher-level cognitive functions via five parallel frontal–subcortical circuits (i.e., skeletomotor, oculomotor, dorsolateral prefrontal, orbitofrontal, and anterior cingulate) (Alexander et al, 1986; Cummings, 1993). In primate models, retrograde labeling of neurons have demonstrated that 1/3 of BG output is directed to prefrontal areas (i.e., BA regions 9, 46, and lateral aspect of 12), including multiple areas of the prefrontal cortex (PFC) that are critical to functions such as language production (Crescentini, Lunardelli, Mussoni, Zadini, & Shallice, 2008). Understanding the neuroanatomical correlates of selective language functions is the first step to improving the assessment and identification of language disturbances that may arise from neurological insult to the basal ganglia (BG), or from diseases that preferentially target BG functions (e.g., Human Immunodeficiency Virus-Type 1 [HIV-1], Huntington’s, and Parkinson’s).…”
Section: Introductionmentioning
confidence: 99%